Review of the family Proctorenyxidae (Hymenoptera: Proctotrupoidea), with description of new species from South Korea - Kim, Chang-Jun; Lelej, Arkady S.; Park, Bia; Lee, Jong-Wook (Zootaxa, 2016)
Kozlov (1994) established a new parasitic proctotrupoid family, Renyxidae, for a single species, Renyxa incredibilis, from Primorskij Krai, in the Russian Far East. A new genus and species, Hsiufuropronia chaoi, was described from China, Beijing (Yang 1997) in the family Roproniidae. Lelej and Kozlov (1999) noticed that Renyxa was preoccupied and was initially used by Kurochkin and Slankis (1973) for a genus of flatworms (Cestoda: Litobothridae). According to Articles 39, 60 of the Code (ICZN 1999), the names of the genus and family were changed to Proctorenyxa Lelej & Kozlov, 1999 (Lelej & Kozlov 1999). He et al. (2002) transferred Hsiufuropronia from Roproniidae to Proctorenyxidae based on Yang’s original description and illustrations, and synonymized Hsiufuropronia Yang under Proctorenyxa Lelej & Kozlov. Later, He and Xu (2015) proposed that the family name Proctorenyxidae should be replaced by Hsiufuroproniidae and the genera Proctonenyxa Lelej & Kozlov and Hsiufuropronia Yang should be separate. However, the replacement name Hsiufuroproniidae contradicts article 39 of the Code (ICZN 1999).